Potential Reduction of CO2 Emissions in Transportation Bus Vehicles with Diesel Fuel and Compressed Natural Gas : Case Study: Fuel Mix Variations - Fikri Fahlevi Nasution; Martin, Awaludin (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
The Indonesian government continues to strive to reduce CO2 emissions, with a target reduction of 29% by 2030. In urban areas, motor vehicles are the largest contributors to CO2 emissions, accounting for 70%. One of the steps that can be taken to reduce CO2 emissions is by using Compressed Natural Gas (CNG) as a vehicle fuel. The purpose of this writing is to study the impact of replacing Diesel Fuel with CNG on the CO2 emissions generated by transportation buses.. Based on the discussion, the CO2 emissions produced by 100 city buses (fuel consumption of 100 L/unit/day) are 26.20 tons of CO2/day, 785.96 tons of CO2/month, and 9,562.56 tons of CO2/year for 100% diesel fuel. For 100% CNG fuel, the emissions are 0.02 tons of CO2/day, 0.63 tons of CO2/month, and 7.72 tons of CO2/year. CO2 emissions are reduced by 2.61 tons of CO2/day, 78.54 tons of CO2/month, and 955.49 tons of CO2/year for every 10% reduction in diesel fuel usage. CO2 emissions can be reduced by up to 99.9% by replacing diesel fuel with CNG. The area of forest required to eliminate CO2 with 100% diesel fuel composition annually is 16.79 hectares, while with 100% CNG composition, it is only 0.01 hectares. The forest area required decreases by 1.67 hectares for every 10% reduction in diesel fuel composition.